2018
DOI: 10.1080/10520295.2018.1463453
|View full text |Cite
|
Sign up to set email alerts
|

Age associated decrease of sialin in salivary glands

Abstract: Aging salivary glands are characterized by a reduced volume of acini, increased duct volume, decline in the rate of synthesis of proteins and their mRNA, and decreased saliva flow. Sialin is a versatile anion transporter that is highly expressed in salivary glands and may also participate in maintenance of salivary gland function. We investigated age-associated sialin expression in salivary glands. Submandibular glands of mice and human parotid gland were collected at different ages. Western blot and real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…For example, in rodents the effects of dietary NO3are more prominent in fast-vs. slow-twitch muscle (4,5), and some (25,26), but not all (27), studies of humans have found that aging results in a reduction in the percentage of fast-twitch muscle fibers. Alternatively and/or in addition, an age-related decrease in the ability of salivary glands to concentrate NO3 - (28) or more rapid destruction of NO due to increased production of reactive oxygen species in aged muscle (29,30) could limit the beneficial effects of dietary NO3in older persons.…”
mentioning
confidence: 99%
“…For example, in rodents the effects of dietary NO3are more prominent in fast-vs. slow-twitch muscle (4,5), and some (25,26), but not all (27), studies of humans have found that aging results in a reduction in the percentage of fast-twitch muscle fibers. Alternatively and/or in addition, an age-related decrease in the ability of salivary glands to concentrate NO3 - (28) or more rapid destruction of NO due to increased production of reactive oxygen species in aged muscle (29,30) could limit the beneficial effects of dietary NO3in older persons.…”
mentioning
confidence: 99%
“…One of these proteins is sialin, a small peptide produced by parotids with an alkalinizing effect that contributes to the increased oral pH. The production of this peptide decreases with aging, 25 and although we have not measured the concentration of sialin in saliva, we suggest that a decrease in salivary pH with aging is associated with a decrease in the amount of sialin in saliva. Another factor that is associated with reduced salivary flow is a higher BMI.…”
Section: Discussionmentioning
confidence: 69%
“…Sialin is a versatile anion transporter expressed in salivary glands [258] that transports glutamate, NO 3 − , and other anions from blood to saliva. We hypothesize that salivary epithelium sequesters the PSMA ligands by uptake through the sialin anion/ H + symporter on the basolateral side of these cells but is not able to secrete the ligands into the saliva at the apical side.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this hypothesis, sialin transports NAAG and a variety of glutamate containing xenobiotics, as well as NO 3 − and glutamate, into epithelial cells [259] , [260] , [261] . Salivary glands also express the most sialin in mammals [258 , 261] whereas the other conduit for PSMA ligand uptake, PSMA, is expressed at very low levels in these glands [10 , 36 , 89] . Moreover, PSMA expression is restricted to intercalated epithelium of these glands [36] .…”
Section: Introductionmentioning
confidence: 99%